2004
DOI: 10.3748/wjg.v10.i20.2963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cigarette smoking on response to interferon therapy in chronic hepatitis C Egyptian patients

Abstract: AIM:Smoking may affect adversely the response rate to interferon-α. Our objective was to verify this issue among chronic hepatitis C patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 32 publications
3
13
1
1
Order By: Relevance
“…Similar results have been reported previously, suggesting that these risk factors can prolong therapy duration which may result in serious side effects [22]. Smoking increases the chances of fibrosis and damage to the liver in patients with chronic hepatitis C [23].…”
Section: Discussionsupporting
confidence: 78%
“…Similar results have been reported previously, suggesting that these risk factors can prolong therapy duration which may result in serious side effects [22]. Smoking increases the chances of fibrosis and damage to the liver in patients with chronic hepatitis C [23].…”
Section: Discussionsupporting
confidence: 78%
“…El-Zayadi et al [18] reported in their study that smoking decreased response to treatment and decreased sustained virological response and explained that by patients with chronic HCV have lower levels of hepatic, plasma and lymphocytic glutathione that favor the hepatotoxic effect of smoking and reduce efficacy of treatment, but current study couldn't conclude these results.…”
Section: Discussioncontrasting
confidence: 55%
“…Smoking was more prevalent in this sample than a normative comparison sample of veterans (45.8% vs 33.9%, respectively) [72]. This finding is particularly important because recent studies suggest that cigarette smoking aggravates liver functioning, increases the risk of liver fibrosis, and decreases the efficacy of IFN treatment [73][74][75]. Alcohol use was also very prevalent in our sample and at an intensity that is described as "risky or hazardous" and in need of further assessment.…”
Section: Discussionmentioning
confidence: 45%